Improving community health networks for people with severe mental illness: a case study investigation - Vanessa Pinfold; Daryl Sweet; Ian Porter; Cath Quinn; Richard Byng; Chris Griffiths; Julie Billsborough; Doyo Gragn Enki; Ruth Chandler; Martin Webber; John Larsen; John Carpenter; et al. (National Institute for Health Research, 2015)
Introduction: Policy drivers in mental health to address personal recovery, stigma and poor physical health indicate that new service solutions are required. This study aimed to understand how connections to people, places and activities were utilised by individuals with severe mental illness (SMI) to benefit health and wellbeing. Methods: A five-module mixed-methods design was undertaken in two study sites. Data were collected from 150 network-mapping interviews and 41 in-depth follow-up interviews with people with SMI; in-depth interviews with 30 organisation stakeholders and 12 organisation leaders; and 44 telephone interviews with practitioners. We undertook a three-stage synthesis process including independent lived experience feedback, and a patient and public involvement team participated in tool design, data collection, analysis and write-up. Results: Three personal network types were found in our study using the community health network approach: diverse and active; family and stable; formal and sparse. Controlled for other factors we found only four variables significantly associated with which network type a participant had: living alone or not; housing status; formal education; long-term sickness or disability. Diagnosis was not a factor. These variables are challenging to address but they do point to potential for network change. The qualitative interviews with people with SMI provided further understanding of connection-building and resource utilisation. We explored individual agency across each network type, and identified recognition of the importance and value of social support and active connection management alongside the risks of isolation, even for those most affected by mental illness. We identified tensions in personal networks, be that relationships with practitioners or families, dealing with the impact of stigma, or frustrations of not being in employment, which all impact on network resources and well-being. The value of connectedness within personal networks of people, place and activity for supporting recovery was evident in shaping identity, providing meaning to life and sense of belonging, gaining access to new resources, structuring routines and helping individuals 'move on' in their recovery journey.: Health-care practitioners recognised that social factors were important in recovery but reported system-level barriers (workload, administrative bureaucracy, limited contact time with clients) in addressing these issues fully. Even practitioners working in third-sector services whose remit involved increasing clients' social connection faced restrictions due to being evaluated by outcome criteria that limited holistic recovery-focused practices. Service providers were keen to promote recovery-focused approaches. We found contrasts between recovery ideology within mental health policy and recovery practice on the ground. In particular, the social aspects of supporting people with SMI are often underprioritised in the health-care system. In a demanding and changing context, strategic multiagency working was seen as crucial but we found few examples of embedded multisector organisation partnerships. Conclusion: While our exploratory study has limitations, findings suggest potential for people with SMI to be supported to become more active managers of their personal networks to support well-being regardless of current network type. The health and social care system does not currently deliver multiagency integrated solutions to support SMI and social recovery. Funding: The National Institute for Health Research Health Services and Delivery Research programme.